Why is there no Asian monetary fund? - Hyun Suk; James F. Paradise (Asian Development Bank Institute (ADBI), 2019)
This study describes the development of regional financial arrangements in Asia and Europe, assesses their effects on financial stability, and draws lessons for Asia from European experience. One of its main conclusions is that Asia needs to develop a more institutionalized multilateral structure as part of a regional financial safety net that also includes foreign exchange reserves and bilateral swap arrangements. Such a structure would have a permanent secretariat and a system of paid-in capital that goes beyond the current CMIM arrangement and might one day evolve into an Asian monetary fund. Obstacles to achieving this include great power rivalries between Japan and the People's Republic of China and lingering concerns about United States opposition to increased Asian autonomy. Lessons from Europe include the need for strong economic surveillance and organizational arrangements that facilitate macroeconomic adjustment and recapitalization of stressed institutions and a reduction in overdependence on the dollar for trade and finance. Absorbing these lessons and designing more effective financial crisis prevention and response mechanisms will be the main task for Asian policy makers ahead as concerns mount about the sustainability of the global economic upswing.
Keywords: F33; F55; F66; 330; Asian financial crisis; global financial crisis; financial safety net; Asian Monetary Fund